EFEKTIVITAS PENERAPAN APLIKASI SISTEM INFORMASI PEMERINTAH DAERAH TERHADAP PENYUSUNAN LAPORAN KEUANGAN PADA DINAS SOSIAL KABUPATEN SUMBAWA BARAT - WIDIASTUTI, SRI; ZULKIEFLIMANSYAH, ZULKIEFLIMANSYAH; UMAR, UMAR (GANEC SWARA, 2023)
This research discusses the obstacles or challenges faced in the application of the Local Government Information System (SIPD) application in the preparation of financial reports at the West Sumbawa Regency Social Service and how the effectiveness of the application of the Local Government Information System (SIPD) application in the process of preparing financial reports at the West Sumbawa Regency Social Service. The purpose of this study is to determine the obstacles or challenges faced in the application of the SIPD application in the preparation of financial reports and analyze the effectiveness of the application of the Local Government Information System (SIPD) application in the process of preparing Financial Statements at the Social Service of West Sumbawa Regency. This research uses mixed methods (combined methods) qualitative methods to determine the obstacles or challenges faced in the application of the SIPD application in the preparation of financial reports and quantitative methods to analyze the effectiveness of the application of the Local Government Information System (SIPD) application in the process of preparing financial reports at the Social Service of West Sumbawa Regency. The results showed that the use of SIPD for the preparation of Financial Statements still has obstacles and challenges, namely it takes longer because SIPD is integrated with applications at the Ministry of Finance and SIPD has incomplete features so that the preparation of Financial Statements must be used simultaneously between SIPD and the Financial Management Information System (FMIS) so that the preparation of Financial Statements, data must be done manually so that it slows down the process and is prone to errors because it requires accuracy in the process of preparing functional SPJ. From the results of the analysis using SPSS, the t test obtained a significance value of 0.842> 0.717 or the value of t count> t table so that it can be concluded that the use of the Local Government Information System Application is not effective on the quality of Financial Statements at the Social Service of West Sumbawa Regency.